FAKE SUBSTITUTION OF PERSONALITY: THE SEARCH FOR BENEFITS OR A WAY OF PSYCHOLOGICAL PROTECTION: virtual reality, fake information, personal self-identification, self-presentation, online identity - Artiushyna, Kateryna (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The article considers the problem of determining the psychological consequences of such a phenomenon as increasing the impact of the virtual environment on the life of modern man, one of the manifestations of which is the widespread dissemination of fake information in the information environment. The purpose of the study is to reveal the need to identify the attitudes of young people to fake information, to specify the reasons that cause young people to turn to the procedure of designing their online identity. The objectives of the study are to identify and analyze modern theoretical views on this problem, to build a theoretical model of the motives for creating fake accounts by students, to develop an appropriate questionnaire based on it. Research methods were: theoretical analysis, content analysis, theoretical modeling, discussion, conversations, surveys. As a result of the analysis of modern works on the relevant topics and the real practice of such information, it was found that, in addition to clearly negative manifestations, today the problem of substituting natural processes of personal identity formation with online identity is becoming increasingly important. Designing an online identity, which becomes the basis of self-presentation, is a means of psychological protection that allows a particular person to overcome their psychological problems. Therefore, today it is important to create a methodological framework for the study of this process, conducting special studies to identify the attitudes of people of different ages and social groups to fake information, training practical psychologists to work with people with online identity. As a result of the conducted search experiment the initial methodical means of carrying out such researches among modern youth are defined